Measurements of the trilinear gauge boson couplings WWV (V equivalent to gamma,Z) in e(+)e(-) collisions at 183 GeV - Abreu, P; Adam, W; Adye, T; Adzic, P; Ajinenko, I; Albrecht, Z; Alderweireld, T; Alekseev, G; Alemany, R; Allmendinger, T; Allport, P; Almehed, S; et al. (1999)
Measurements of the trilinear gauge boson couplings WWγ and WWZ are presented from data taken by DELPHI in 1997 at an energy of 183 GeV. From a study of the reactions e+ e- →W+W-, e+e- → Wev and e+ e-→ vvy, values are obtained for Δg1Z and Δκγ, the differences of the WWZ charge coupling and of the WWγ dipole couplings from their Standard Model values, and for λγ, the WWγ quadrupole coupling. The observations are consistent with the predictions of the Standard Model. © 1999 Elsevier Science B.V. All rights reserved.